2006
DOI: 10.1099/mic.0.28794-0
|View full text |Cite
|
Sign up to set email alerts
|

Data mining and characterization of a novel pediocin-like bacteriocin system from the genome of Pediococcus pentosaceus ATCC 25745

Abstract: The genome of Pediococcus pentosaceus ATCC 25745 contains a gene cluster that resembles a regulated bacteriocin system. The gene cluster has an operon-like structure consisting of a putative pediocin-like bacteriocin gene (termed penA) and a potential immunity gene (termed peiA). Genetic determinants involved in bacteriocin transport and regulation are also found in proximity to penA and peiA but the so-called accessory gene involved in transport and the inducer gene involved in regulation are missing. Consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 52 publications
2
42
0
4
Order By: Relevance
“…Correction of a mutation in a gene required for bacteriocin synthesis has been used successfully to identify a new bacteriocin in lactic acid bacteria (23). The genome of Pediococcus pentosaceus ATCC 25745 contains a gene cluster that resembles a regulated bacteriocin system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correction of a mutation in a gene required for bacteriocin synthesis has been used successfully to identify a new bacteriocin in lactic acid bacteria (23). The genome of Pediococcus pentosaceus ATCC 25745 contains a gene cluster that resembles a regulated bacteriocin system.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in production of antimicrobial activity is often due to a dysfunctional genetic system. Occasionally, it has been observed that bacterial genomes encode only parts of the bacteriocin production system or that mutations have inactivated the functionality of the bacteriocin genes (23,85).…”
Section: Peptide Bacteriocin Genes In Genome Sequencesmentioning
confidence: 99%
“…1B). Abolished bacteriocin production due to defects in the regulatory genes has been reported for Pediococcus pentosaceus ATCC 25745, and when this bacterium was complemented with an intact gene by cloning, normal bacteriocin production was restored (11). Similarly, to investigate whether the lack of active bacteriocins could result from no or low gene expression, the bacteriocin locus (GenBank accession no.…”
Section: Reanalysis Of the Abi Protein Family Each Protein Family Inmentioning
confidence: 99%
“…This strategy has previously proven successful for heterologous production of both one-and two-peptide bacteriocins (5,11,29,36 Fig. 5A.…”
Section: Reanalysis Of the Abi Protein Family Each Protein Family Inmentioning
confidence: 99%
“…Peptides in subgroup 3 as well as enterocin SE-K4 and carnobacteriocin B2 in subgroup 4 exceptionally have neither the conserved tryptophan at the C-tails, nor the cysteine residues to form the C-terminal disulfide bridge (Table 2). Marrec et al 2000Metivier et al 1998Aymerich et al 1996Henderson et al 1992Marugg et al 1992Tichaczek et al 1994Kalmokoff et al 2001Birri et al 2010Feng 2009Kawamoto et al 2002Bennik et al 1998Yamazaki et al 2005Bhugaloo-Vial et al 1996Jack et al 1996Vaughan et al 2001Fimland et al 2002bHeng et al 2007 Subgroup 2 Kwaadsteniet et al 2006Quadri et al 1995Eguchi et al 2001Diep et al 2006 The YGNGV/L "pediocin box" is marked (bold), the leucine residue (L), odd, and uncertain amino acids (X) are marked as bold and red. Names of the six newly identified class IIa bacteriocins are in red (Rea et al 2011).…”
Section: Class Iia Bacteriocinsmentioning
confidence: 99%